2006
DOI: 10.1002/ijc.22148
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk among US radiologic technologists, 1983–1998

Abstract: While exposure to moderate to high-dose ionizing radiation is an established risk factor for lung cancer, the relationship between lung cancer and chronic low dose radiation remains uncertain. We examined lung cancer risk among 71,894 US radiologic technologists who were certified during 1926-1982, responded to a baseline questionnaire (1983)(1984)(1985)(1986)(1987)(1988)(1989), and were free of cancer other than non-melanoma skin cancer at baseline. Study participants were followed until completion of a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, several studies have not shown an increased risk of lung cancer: physicians in the British Radiological Society (Berrington et al , 2001); US radiological technicians (Rajaraman et al , 2006); nuclear industry workers (Carpenter et al , 1994; Omar et al , 1999); the National Registry for Radiation Workers (Muirhead et al , 1999); and combined analysis of UK, USA and Canadian studies (Cardis et al , 1995). …”
Section: Methodsmentioning
confidence: 99%
“…However, several studies have not shown an increased risk of lung cancer: physicians in the British Radiological Society (Berrington et al , 2001); US radiological technicians (Rajaraman et al , 2006); nuclear industry workers (Carpenter et al , 1994; Omar et al , 1999); the National Registry for Radiation Workers (Muirhead et al , 1999); and combined analysis of UK, USA and Canadian studies (Cardis et al , 1995). …”
Section: Methodsmentioning
confidence: 99%
“…Radiation is a risk factor that is responsible for increased incidence of cancer among healthcare staff working in a radiology department. The US Radiologic Technologist Health Study observed between 1983 and 1998 that there was an increased rate of breast cancer among female radiographers [9]. The study found out that lead aprons provided no protection to the axillary region or the lateral aspect of the breast especially in individuals with large breasts [10].…”
Section: Introductionmentioning
confidence: 99%
“…There was little evidence of exposure-response for thyroid cancer ( 11 ) and lung cancer ( 12 ). The overall results, based on work history as a surrogate for occupational radiation exposure, suggested an exposure-response relation because risks were elevated among those employed in earlier years when radiation exposures were highest.…”
Section: Introductionmentioning
confidence: 99%